Agricultural Information System Design For Bojonegoro Regency Using Prototype Method (International Journal of Business and Information Technology, 2022)
With the increasingly sophisticated information technology available for the public to access, easier it is for the public to know what is available and what is desired. The use of this information technology has also been used by the public to publicize the potential of a company and institution. Access to information technology on agricultural products is still lacking, which makes it difficult for the Department of Agriculture to market agricultural products directly to the public. With this information system, it is hoped that it will help the agricultural office in the Bojonegoro city area to record the harvests of farmers in the Bojonegoro area precisely and accurately. The making of this information system is assisted by using the prototype method. This research produces an information system that can manage data on agricultural products in the Bojonegoro area which will be managed by the Bojonegoro Food and Agriculture Security Service.